Evidence-based exercise recommendations to improve functional mobility in older adults - A study protocol for living systematic review and meta-analysis [version 2; peer review: 2 approved] - Claudia Volecker-Rehage; Uros Marusic; Bettina Wollesen; Antoine Langeard; Tamar Yellon; Anna Wunderlich; Vera Belkin; Guoping Qian; Eleftheria Giannouli; Zbigniew Ossowski; Rafael A. Bernades; Yael Netz; et al. (Open Research Europe)
Background and objectives This is a protocol for a living systematic review and meta-analysis. This review will assess the effects of state-of-the-art exercise interventions designed to promote functional mobility. Therefore, after identifying all potential interventions, we will use the F.I.T.T. principles (frequency, intensity, time, type) as well as the physical and health status of the participants as moderators to analyse the mechanisms for the positive benefits of exercise interventions. The main research questions are: Which exercise types are most beneficial for improving functional mobility in various populations of older adults? Which physical exercise characteristics in terms of frequency, intensity, time and duration will achieve the greatest benefit in terms of the defined outcomes, i.e, the functional mobility of older adults? Methods The systematic literature research according to PRISMA guidelines will search databases like MEDLINE, APA Psych-Info and Web of Science. Inclusion criteria are: healthy older people ≥ 50 years, randomized-controlled trials including exercise intervention and a walking or mobility assessments (eg., TUG, SPPB) as an outcome measure. A preliminary search revealed more than 33,000 hits that will be screened by pairs of independent reviewers. The results will be summarized according to the effects regarding functional mobility and potential dose-response relations via respective meta-analysis. Conclusion The systematic review will comprise the knowledge of the existing literature with regards to the effects of the physical activity interventions compared to an active or inactive control group. We will summarize the effects with respect to the F.I.T.T.. They provide a foundation for structuring an optimal exercise training program. If possible, we will also compare interventions from the different categories (eg. cardiovascular, resistance, motor-coordinative, multicomponent or mind-body exercise) as a network analysis and report the influence of moderator variables. Based on the results evidence-based guidelines following GRADE for physical exercise interventions to improve functional mobility in older adults will be provided.